SINTESIS KOMPOSIT POLIANILINA/ELECTROCHEMICALLY EXFOLIATED GRAPHENE SEBAGAI ELEKTRODA LAWAN PADA DYE SENSITIZED SOLAR CELL - Ikhsanul Fatya, Alvian
Nowadays, conducting polymers have attracted great interest in Platinum free Dye Sensitized Solar Cell (Pt-free DSSC) application. They act as a counter electrode which serves charge transfer from the external circuit to regenerate the redox couple (e.g. I"/h"). Polyaniline (PANI) is one of the most intensively studied conducting polymers due to its good electrocatalytic activity and environmental stability. However, it has low electrical conductivity so that it is usually combined with other materials to be a good counter electrode. PANVgraphene composite is an altemative choice of counter electrode material for Pt-free DSSC. The combination of good electrocatalytic activity of PANI and high electrical conductivity of graphene will produce a DSSC system with excellent perfom1ance. However, the production of graphene using common Hummer's method is time-consuming and produces a lot of waste. In this study, we used the electrochemical method to obtain electrochemically exfoliated graphene (EEG) and fabricate the PANVEEG composite as the counter electrode. The graphite rod from used batteries was electrochemically exfoliated in the H2S04 solution to obtain EEG suspension. Synthesis of PANI was carried out using the mixed method in that EEG suspension. Raman spectra show that the PANVEEG composite was successfu lly synthesized indicated by the presence of their characteristic peaks. DC measurement reveals that EEG has conductivity of 1 S/cm. Current density-voltage (J-V) measurements show that the power conversion efficiency of PANI/EEG composite (1.79%) better than the PANI-based counter electrode (1.15%). This enhancement is due to the good electrical conductivity of EEG. The more EEG added, the more DSSC perfonnance increases. There is also a linear relationship between increased DSSC efficiency and increased electrical conductivity from PANIIEEG composite. This increase shows the direct effect between the electrical conductivity of the counter electrode on DSSC perfonnance.